Literature study: Relationship between pharmacist's "pharmaceutical care" and achievement of blood pressure targets in hypertension patients - Sriwantika, Ika; Mulyani, Yani; Patonah, Patonah (Science Midwifery, 2024)
Hypertension is defined by persistently elevated arterial blood pressure. The Seventh Report of the Joint National Committee (JNC VII) on Detection, Evalution, and Treatment of High Blood Pressure explains that hypertension is a condition where there is an increase in blood pressure in the arteries above 140/90 mmHg. The general goal of hypertension treatment is to reduce mortality and morbidity associated with hypertension. Mortality and morbidity are related to target organ damage. Reducing risk is the main goal of hypertension therapy, and the choice of drug therapy is significantly influenced by evidence showing risk reduction. The target blood pressure value recommended in JNC VII for most patients is < 140/90 mm Hg, patients with diabetes < 130/80 mm Hg and patients with chronic kidney disease < 130/80 mm Hg. One part of the therapeutic management of hypertensive patients to achieve therapeutic goals is through pharmaceutical care (Pharmaceutical care). Counseling as an implementation of the concept of pharmaceutical care (pharmaceutical care) aims to provide additional knowledge about drugs and treatment with the hope of providing patients with an understanding of the role of drugs in curing their disease. This review summarizes the results of research on the effect of pharmacist intervention on achieving blood pressure targets for hypertensive patients by searching international and national published scientific journals from the last year 2010- 2021 via electronic databases in the form of Pubmed, ScienceDirect and Google Scholar.